2017
DOI: 10.1007/s11104-017-3440-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutualism between Klebsiella SGM 81 and Dianthus caryophyllus in modulating root plasticity and rhizospheric bacterial density

Abstract: Aims Dianthus caryophyllus is a commercially important ornamental flower. Plant growth promoting rhizobacteria are increasingly applied as bio-fertilisers and bio-fortifiers. We studied the effect of a rhizospheric isolate Klebsiella SGM 81 strain to promote D. caryophyllus growth under sterile and non-sterile conditions, to colonise its root system endophytically and its impact on the cultivatable microbial community. We identified the auxin indole-3-acetic acid (IAA) production of Klebsiella SGM 81 as major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Abdel-Salam et al (2013) reported B. licheniformis strain having pqq gene with expected amplified PCR product of 1202 bp for efficient phosphate solubilization. According to Gang et al (2017) Klebsiella SGM81 strain showed the presence of ipdc gene and confirmed bacterial production of IAA with improvement in PGP traits of D. caryophyllus . In addition to acds gene, various strains of Mesorhizobium , Rhizobium , Sinorhizobium , Microbacterium , Klebsiella , Enterococcus , and Pseudomonas etc .…”
Section: Discussionmentioning
confidence: 73%
“…Abdel-Salam et al (2013) reported B. licheniformis strain having pqq gene with expected amplified PCR product of 1202 bp for efficient phosphate solubilization. According to Gang et al (2017) Klebsiella SGM81 strain showed the presence of ipdc gene and confirmed bacterial production of IAA with improvement in PGP traits of D. caryophyllus . In addition to acds gene, various strains of Mesorhizobium , Rhizobium , Sinorhizobium , Microbacterium , Klebsiella , Enterococcus , and Pseudomonas etc .…”
Section: Discussionmentioning
confidence: 73%
“…The details of K.q. SGM81 sequence (PRJEB21197) are mentioned in our previous manuscript [ 9 ]. K.q.…”
Section: Methodsmentioning
confidence: 99%
“…The few main mechanisms of the rhizosphere that influence N-uptake efficiency are: root size morphology, root N transporter system, and interaction of root–microorganisms such as plant growth-promoting bacteria (PGPB) [ 7 ]. Many PGPBs are reported to positively improve root system development by manipulating plant hormones such as auxins, cytokinins, or gibberellins [ 8 , 9 ], and hence the acquisition of some nutrients. NO 3 − and NH 4 + uptake systems may be enhanced by the interaction with arbuscular mycorrhizal fungi (AMF), PGPB, and some organic acids [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Again, incubate the plates at 25 °C in 14 h light and 10 h dark cycles in a plant culture room. Salkowski reagent shows a maximum yield to 215 μg•ml -1 detected after 72 h with 0.15% tryptophan (Figure 1a in Gang et al, 2018).…”
Section: Transfer the Treated Plants Onto New Ms Agar Medium Devoid Of Iaa And Sucrose In Squarementioning
confidence: 99%